A eutectic mixture of choline chloride and urea as an assisting solvent in the synthesis of flower-like hierarchical BiOCl structures with enhanced photocatalytic activity. Issue 61 (4th July 2015) - Ge, Jianhua; Guo, Xuetao; Xu, Xin; Zhang, Pingping; Zhu, Jingling; Wang, Jingbo
<x xml:space="preserve">Abstract</x> Flower-like hierarchical BiOCl structures were successfully synthesized in the presence of a eutectic mixture of choline chloride and urea through a solvothermal process.